Adobe Flash Application Development to Improve Mathematics Learning Outcomes For Class V - Sasmita, Lisa Dwi; Sutaryono, Sutaryono (Elementary School Teacher, 2021)
This study at developing instructional media, test the viability and effectiveness of adobe flash-based multimedia on cube and block nets for the fifth students at Candi Elementary School. The method used Research and Development (RD). The results showed that adobe flash-based multimedia can be used in learning based on the content expert's assessment obtained a percentage of 74% and by media expert assessment obtained a percentage of 75%, both in viable category. The results of the adobe flash-based multimedia was effectively used in accordance with the results obtained with the value = 4.867 and = 2.045. From the calculation, obtained = 4.867 = 2.045, so, H0 was rejected and Ha was accepted. The results of N-gain data was 0.34 in moderate criteria..Keywords: Adobe Flash, Learning Media; Mathematics; Multimedia